2016
DOI: 10.21037/atm.2016.05.31
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of prostate cancer: a tale of rare variants and common single nucleotide polymorphisms

Abstract: Prostate cancer (PCa) is the most common non-skin cancer men in developed countries. Despite years of research, no strong modifiable risk factor for PCa has been found. The two most significant cancer risk factors, smoking and obesity, do not appear to be strong risk factors for PCa. A recent systematic review and meta-analysis summarized the current literature of tobacco use and PCa mortality and incidence (1). This meta-analysis included 51 cohort studies (50,349 incident cases and 4,082,606 cohort participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…18. It has long been known that age is a significant risk factor for prostate cancer, but GWAS studies have shown that there is a significant genetic component [64]. Additionally, it has been shown, using genome wide complex trait analysis (GCTA), that variants with minor allele frequency 0.1 − 1% make up an important contribution to "missing heritablity" for men of African ancestry [65].…”
Section: Testing Using Genetically Dissimilar Subgroups: Ancestry Omentioning
confidence: 99%
“…18. It has long been known that age is a significant risk factor for prostate cancer, but GWAS studies have shown that there is a significant genetic component [64]. Additionally, it has been shown, using genome wide complex trait analysis (GCTA), that variants with minor allele frequency 0.1 − 1% make up an important contribution to "missing heritablity" for men of African ancestry [65].…”
Section: Testing Using Genetically Dissimilar Subgroups: Ancestry Omentioning
confidence: 99%
“…As with breast cancer, the fraction of PC attributed to highly malignant mutations is low. Known rare, higheffect-size variants such as BRCA1/2, ATM, and HOXB13 explain only 10-12% of heritability (Wu and Gu, 2016;Mancuso et al, 2016;Walsh, 2017;Lecarpentier et al, 2017). Recently, Eeles et al (2017) using an imputed meta-analysis for 145,000 men, reported that the GWAS polygenic score they obtained explains 33% of the familial relative risk.…”
Section: Prostate Cancer (Pc)mentioning
confidence: 99%
“…Recently, Eeles et al (2017) using an imputed meta-analysis for 145,000 men, reported that the GWAS polygenic score they obtained explains 33% of the familial relative risk. Wu and Gu (2016) concluded that the search for the missing heritability may be better served by high-coverage whole-genome sequencing (WGS); however, due to the cost and complexity, it is not currently feasible to obtain this much high-quality data. In the absence of more predictive genetic data, Wu and Gu (2016) noted that the best predictor of PC is age itself.…”
Section: Prostate Cancer (Pc)mentioning
confidence: 99%
See 2 more Smart Citations